The Communication System of Building from Outdoor to Indoor with AMC at 10 GHz - Andrita Ceriana Eska (JURNAL INFOTEL, 2020)
The propagation model of communication systems was used propagation from outdoor to indoor of building. In the inside that building used partition with brick. That propagation condition used downlink condition from mobile station side. The communication frequency used 10 GHz. Some parameter variation was used in this research such as radio base station coverage, mobile station location of building, and code rate communication. The coverage variation of radio base station used femtocell and picocell. As the result described signal to noise ratio (SNR)at every node communication, adaptive modulation and coding (AMC) variation, and coverage area percentage in the building. The modulation and coding scheme (MCS) was used consist of QPSK, 16 QAM, and 64 QAM